2D PtS nanorectangles/g-C3N4 nanosheets with a metal sulfide–support interaction effect for high-efficiency photocatalytic H2 evolution. Issue 2 (11th December 2020) - Lin, Bo; Zhou, Yao; Xu, Baorong; Zhu, Chao; Tang, Wu; Niu, Yingchun; Di, Jun; Song, Pin; Zhou, Jiadong; Luo, Xiao; Kang, Lixing; Duan, Ruihuan; et al.
Abstract : 2D PtS nanorectangles/g-C3 N4 nanosheets with a metal sulfide–support interaction effect achieve an ultrahigh photocatalytic H2 evolution rate. Abstract : Cocatalyst design is a key approach to acquire high solar-energy conversion efficiency for photocatalytic hydrogen evolution. Here a new in situ vapor-phase (ISVP) growth method is developed to construct the cocatalyst of 2D PtS nanorectangles (a length of ∼7 nm, a width of ∼5 nm) on the surface of g-C3 N4 nanosheets. The 2D PtS nanorectangles/g-C3 N4 nanosheets (PtS/CN) show an unusual metal sulfide–support interaction (MSSI), which is evidenced by atomic resolution HAADF-STEM, synchrotron-based GIXRD, XPS and DFT calculations. The effect of MSSI contributes to the optimization of geometrical structure and energy-band structure, acceleration of charge transfer, and reduction of hydrogen adsorption free energy of PtS/CN, thus yielding excellent stability and an ultrahigh photocatalytic H2 evolution rate of 1072.6 μmol h −1 (an apparent quantum efficiency of 45.7% at 420 nm), up to 13.3 and 1532.3 times by contrast with that of Pt nanoparticles/g-C3 N4 nanosheets and g-C3 N4 nanosheets, respectively. This work will provide a new platform for designing high-efficiency photocatalysts for sunlight-driven hydrogen generation.